Clinical efficacy of long-term treatment in patients with vascular dementia - I. A. Suvorova (Бюллетень сибирской медицины, 2011)
To study efficacy and safety of prolonged course of cerebrolysin therapy in vascular dementia, 48 patients, aged from 59—77 years, with mild and moderate dementia have been studied. A potential of 3-years course of cerebrolysin therapy to slow down the progression of cognitive impairment in patients with vascular dementia has been studied in the open study. Efficacy and safety of cerebrolysin were assessed clinically and with a battery of widespread scales and neuropsychological tests. The improvement of cognitive, functional and motor activities in patients with mild and moderate dementia indicate the high effectiveness of cerebrolysin. A prolonged therapy allows to prevent the progression of cognitive impairment and development of vascular dementia.